PENYIDIKAN TERHADAP TINDAK PIDANA PELANGGARAN WARNET YANG TIDAK MEMILIKI IZINPERATURAN DAERAH KOTA PEKANBARU NOMOR 6 TAHUN 2015 TENTANG PENATAAN DAN PENGELOLAAN PENYELENGGARAAN MENARA TELEKOMUNIKASI . - Vaternus Irwanto Gultom; Mexsasai Indra; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The development of Computer Technology, telecommunication, andinformation has been running in such a way that at this time has been very muchdifferent from previous years. The increasing growth of business activities in thetelecommunication sector makes the government need to do structuring andcontrolling for the realization of postal and telecommunication services thatquality, efficient and positive impact for the community. Based on Article 1 point44 of Pekanbaru City Regulation No. 6 of 2015 on the Management andArrangement of the Telecommunication Tower Operation. Based on theobservations, the authors found several cafes that do not have permission. Basedon the above background, the authors are interested to examine this issue with thetitle "Investigation Against Criminal Violation of Regional Regulation PekanbaruCity No. 6 of 2015 About Structuring and Management of TelecommunicationTower Operation in terms of cafe who do not have permission."The problem of this research are: First, how is the implementation ofcriminal investigation on internet cafe business which is not licensed based on theRegional Regulation of Pekanbaru Number 6 Year 2015 on Setup andManagement of Telecommunication Tower Operation in Pekanbaru City? Second,how is the criminal liability for internet cafe that does not have permission basedon Pekanbaru Regulation No. 6 of 2015 on Setup and Management ofTelecommunication Tower Operation? Thirdly, what are the obstacles of criminalinvestigation to internet cafe business which is not licensed based on PekanbaruRegulation No. 6 of 2015 on Management and Arrangement ofTelecommunication Tower Operation?This type of research is empirical research, another term used issociological legal research also called field research. This sociological lawresearch is based on primary data. Primary data / basic data is data that can bedirectly from the community as the first source through through field research.Based on the results of the study authors concluded that the implementationof the criminal provisions are still not well implemented, criminal accountabilitywas not there. Only limited warning and closure only to restaurants that do nothave a business license.